Lifestyles, arterial aging, and its relationship with the intestinal and oral microbiota (MIVAS III study): a research protocol for a cross-sectional multicenter study - Lugones-Sánchez, Cristina; Santos-Mínguez, Sandra; Salvado, Rita; González-Sánchez, Susana; Tamayo-Morales, Olaya; Hoya-González, Amaya; Ramírez-Manent, José I.; Magallón-Botaya, Rosa; Quesada-Rico, José A.; Garcia-Cubillas, Miriam D.; Rodríguez-Sánchez, Emiliano; Gómez-Marcos, Manuel A.; et al. (Frontiers in Public Health, 2023)
Background The microbiota is increasingly recognized as a significant factor in the pathophysiology of many diseases, including cardiometabolic diseases, with lifestyles probably exerting the greatest influence on the composition of the human microbiome. The main objectives of the study are to analyze the association of lifestyles (diet, physical activity, tobacco, and alcohol) with the gut and oral microbiota, arterial aging, and cognitive function in subjects without cardiovascular disease in the Iberian Peninsula. In addition, the study will examine the mediating role of the microbiome in mediating the association between lifestyles and arterial aging as well as cognitive function. Methods and analysis MIVAS III is a multicenter cross-sectional study that will take place in the Iberian Peninsula. One thousand subjects aged between 45 and 74 years without cardiovascular disease will be selected. The main variables are demographic information, anthropometric measurements, and habits (tobacco and alcohol). Dietary patterns will be assessed using a frequency consumption questionnaire (FFQ) and the Mediterranean diet adherence questionnaire. Physical activity levels will be evaluated using the International Physical Activity Questionnaire (IPAQ), Marshall Questionnaire, and an Accelerometer (Actigraph). Body composition will be measured using the Inbody 230 impedance meter. Arterial aging will be assessed through various means, including measuring medium intimate carotid thickness using the Sonosite Micromax, conducting analysis with pulse wave velocity (PWA), and measuring pulse wave velocity (cf-PWV) using the Sphygmocor System. Additional cardiovascular indicators such as Cardio Ankle Vascular Index (CAVI), ba-PWV, and ankle-brachial index (Vasera VS-2000®) will also be examined. The study will analyze the intestinal microbiota using the OMNIgene GUT kit (OMR−200) and profile the microbiome through massive sequencing of the 16S rRNA gene. Linear discriminant analysis (LDA), effect size (LEfSe), and compositional analysis, such as ANCOM-BC, will be used to identify differentially abundant taxa between groups. After rarefying the samples, further analyses will be conducted using MicrobiomeAnalyst and R v.4.2.1 software. These analyses will include various aspects, such as assessing α and β diversity, conducting abundance profiling, and performing clustering analysis. Discussion Lifestyle acts as a modifier of microbiota composition. However, there are no conclusive results demonstrating the mediating effect of the microbiota in the relationship between lifestyles and cardiovascular diseases. Understanding this relationship may facilitate the implementation of strategies for improving population health by modifying the gut and oral microbiota. Trial registration clinicaltrials.gov/ct2/show/NCT04924907, ClinicalTrials.gov, identifier: NCT04924907. Registered on 21 April 2021.